Synthesis and nucleation studies on L‐leucine hydrobromide: a promising nonlinear optical material. (1st December 2014) - Rani, Radha; Thukral, Kanika; Krishna, Anuj; Sharma, Geetanjali; Vijayan, Narayanasamy; Rathi, Brijesh; Bhagavannarayana, Godavarthi
<x xml:space="preserve">Abstract</x> To achieve good quality bulk size crystal growth, an assessment of the nucleation kinetics of a semi‐organic L‐leucine hydrobromide (L‐LHBr) crystal was carried out using double‐distilled water as solvent medium. The effect on metastable zone width (MSZW) with increasing temperature and on induction period with varied supersaturation level was determined experimentally and was found to be very well in accordance with the nucleation theory prospects. Thereafter, various other nucleation parameters, such as Gibbs free energy and interfacial energy, were also determined. The knowledge of these nucleation parameters indicated the requisite temperature domain and the appropriate growth technique, leading to the successful single‐crystal growth of L‐LHBr by slow cooling in the temperature range 298–291 K. The cooling rate of 0.25 K per day was optimized after repeated trials. X‐ray diffraction and Raman analysis were performed on grown crystals for the verification of the material. High‐resolution X‐ray diffraction analysis was used to assess the crystalline perfection of the grown crystals. To further explore the properties of the grown crystals, photoluminescence and time decay studies, etching analysis, and Z‐scan measurements were performed.